Sequel as A Type of Metatext Practice: Philosophical Perspective - Vladimirovna Khorosheva, Natalia (2021)
The article considers the phenomenon of the sequel as a type of metatext practice and as an integral component in the chain of knowledge transfer. The reproducibility of the original text is thus correlated with "unlimited" semiosis / interpretation. The phenomenon of metatext is closely related to the functioning of secondary texts, since any metatext belongs to the category of secondary texts. By secondary, we mean text created as a result of processing the original, primary text.The sequel acts as a secondary text, and the text that interprets the main text. The relevance of the research, therefore, is related to such philosophical and linguistic problems as reference and interpretation. The popularity of sequels written by modern authors to Jane Austen's novels can be seen as a particular manifestation of the general "fashion" for secondariness. Consciously or not, modern "successors" of her novels tend to repeat her style, even if they simply borrow the characters and plot of the novels. Within the framework of semiotics, the sequel can be considered as a "sign" that displays its referent - the novels of Austen. However (from the point of view of stylistics), the sequel cannot be an exact copy of its original, since it is invariably created in other socio-cultural conditions. A sequel as a sign can display its referent (novel) in three main types: index, icon, symbol, and their combinations. Thus, the article analyzes each of the ways of display and concludes that it is impossible to symbolically reflect the proto-text on the example of the novel "Pride and prejudice" and its sequels written by contemporary authors. One of the results of the work is the assumption that the ontological status of the new "possible world" in the sequel and therefore its communicative success, are in direct correlation with the way of referential representation of the original.